An assessment of the efficacy of camera traps for studying demographic composition and variation in chimpanzees (Pan troglodytes). Issue 9 (8th August 2018) - McCarthy, Maureen S.; Després‐Einspenner, Marie‐Lyne; Samuni, Liran; Mundry, Roger; Lemoine, Sylvain; Preis, Anna; Wittig, Roman M.; Boesch, Christophe; Kühl, Hjalmar S.
Abstract : Demographic factors can strongly influence patterns of behavioral variation in animal societies. Traditionally, these factors are measured using longitudinal observation of habituated social groups, particularly in social animals like primates. Alternatively, noninvasive biomonitoring methods such as camera trapping can allow researchers to assess species occupancy, estimate population abundance, and study rare behaviors. However, measures of fine‐scale demographic variation, such as those related to age and sex structure or subgrouping patterns, pose a greater challenge. Here, we compare demographic data collected from a community of habituated chimpanzees ( Pan troglodytes verus ) in the Taï Forest using two methods: camera trap videos and observational data from long‐term records. By matching data on party size, seasonal variation in party size, measures of demographic composition, and changes over the study period from both sources, we compared the accuracy of camera trap records and long‐term data to assess whether camera trap data could be used to assess such variables in populations of unhabituated chimpanzees. When compared to observational data, camera trap data tended to underestimate measures of party size, but revealed similar patterns of seasonal variation as well as similar community demographic composition (age/sex proportions) and dynamics (particularly emigration and deaths) during the study period. Our findings highlight the potential and limitations of camera trap surveys for estimating fine‐scale demographic composition and variation in primates. Continuing development of field and statistical methods will further improve the usability of camera traps for demographic studies. Abstract : (i) We assessed camera trap measures of chimpanzee party size and group composition by comparing them with observational data onhabituated chimpanzees. (ii) Camera traps underestimated party size but showed similar seasonal variation, group composition, and changes. Seasonal variation in chimpanzee party size, as measured using observational and camera trap data.